An Online Detection Framework for Cyber Attacks on Automatic Generation Control - Huang, Tong; Satchidanandan, Bharadwaj; Kumar, P. R.; Xie, Le (IEEE transactions on power systems, 2018)
We propose an online framework to detect cyberattacks on automatic generation control. A cyberattack detection algorithm is designed based on the approach of dynamic watermarking. The detection algorithm provides a theoretical guarantee of detection of cyberattacks launched by sophisticated attackers possessing extensive knowledge of the physical and statistical models of targeted power systems. The proposed framework is practically implementable, as it needs no hardware update on generation units. The efficacy of the proposed framework is validated in both four-area system and 140-bus system.